Productivity nutritive value and economic potential of irrigatedf odder in two regions of Ghana - Amole, Tunde A.; Panyan, E.; Adekeye, Adetayo Bamikole; Ayantunde, Augustine A.; Duncan, Alan J.; Blümmel, Michael (Wiley, 2022)
An on‐farm study was conducted in the northern and Upper East regions of Ghana to investigate the productivity and nutritive value of irrigated ruzi grass [Urochloa ruziziensis (R. Germ. and C.M. Evrard) Crins] (syn. Brachiaria ruziziensis (R. Germ. and C.M. Evrard)] and forage sorghum (Sorghum almum) grasses as options against dry season feed scarcity and to understand associated market opportunities. Sixty participating farmers each established 100‐m2 plots which were sown at 15 kg ha–1 drilled in 60‐cm rows in the dry season of 2016 and 2017. Irrigation was by flooding of soil surface every alternate day throughout the period of the trial. At both regions, herbage accumulation and nutritive value of forage species were determined at four harvesting stages: 4, 8, 12, and 16 weeks after planting (WAP) followed by 4‐wk intervals between harvests. At the end of the trial, fresh biomass was weighed, bundled, and sold in major livestock feed markets to estimate market price. Allowing forages to establish for only 8 wk resulted in two 4‐wk regrowth harvests with dry matter accumulation (DMA) ranging from 4.5 to 8.1 Mg DM ha–1 from both species and in both regions. Generally, herbage nutritive values in terms of crude protein, metabolizable energy (ME) concentration, and in vitro digestible organic matter (IVDOM) declined (P < .05) while DMA increased linearly with delay in harvest. While both grasses adapted well in the regions under irrigation, 8 WAP harvests provided the best balance between nutritive value and DMA. Irrigated fodder must be marketed more effectively since currently market prices are not closely related to nutritive value.